Melanoma in congenital melanocytic naevi. (1st May 2017) - Kinsler, V.A.; O'Hare, P.; Bulstrode, N.; Calonje, J.E.; Chong, W.K.; Hargrave, D.; Jacques, T.; Lomas, D.; Sebire, N.J.; Slater, O.
Summary: Congenital melanocytic naevi (CMN) are a known risk factor for melanoma, with the greatest risk currently thought to be in childhood. There has been controversy over the years about the incidence of melanoma, and therefore over the clinical management of CMN, due partly to the difficulties of histological diagnosis and partly to publishing bias towards cases of malignancy. Large cohort studies have demonstrated that melanoma risk in childhood is related to the severity of the congenital phenotype. New understanding of the genetics of CMN offers the possibility of improvement in diagnosis of melanoma, identification of those at highest risk, and new treatment options. We review the world literature and our centre's experience over the last 25 years, including the molecular characteristics of melanoma in these patients and new melanoma incidence and outcome data from our prospective cohort. Management strategies are proposed for presentation of suspected melanoma of the skin and the central nervous system in patients with CMN, including use of oral mitogen‐activated protein kinase kinase inhibitors in NRAS ‐mutated tumours.